Targeted Thrombolysis with Magnetic Nanotherapeutics: A Translational Assessment - Ming-Lu Lin; Siao-Yun Wu; Jyh-Ping Chen; Yi-Ching Lu; Shih-Ming Jung; Shiaw-Pyng Wey; Tony Wu; Yunn-Hwa Ma (Pharmaceutics, 2024)
Plasminogen activators, such as recombinant tissue-type plasminogen activators (rtPAs), while effective in treating thromboembolic diseases, often induce hemorrhagic complications due to non-specific enzyme activities in the systemic circulation. This study evaluated the targeting efficiency, efficacy, biodistribution, and potential toxicity of a rtPA covalently attached to chitosan-coated magnetic nanoparticles (chitosan-MNP-rtPA). The thrombolytic activity of a chitosan-MNP-rtPA was preserved by protection from an endogenous plasminogen activator inhibitor-1 (PAI-1) in whole blood and after circulation in vivo, as examined by thromboelastometry. Single-photon emission computed tomography (SPECT) demonstrated real-time retention of a 99mTc-MNP-rtPA induced by magnet application in a rat embolic model; an 80% reduction in rtPA dosage for a chitosan-MNP-rtPA with magnetic guidance was shown to restore blood flow. After treatment, iron deposition was observed in the reticuloendothelial systems, with portal edema and neutrophil infiltration in the liver at a ten-fold higher dose but not the regular dose. Nevertheless, no liver or renal toxicity was observed at this higher dose. In conclusion, the liver may still be the major deposit site of rtPA nanocomposites after targeted delivery; chitosan-coated MNPs are potentially amenable to target therapeutics with parenteral administration.